Phospholipase A2 Activity in Gingival Crevicular Fluid from Patients with Periodontal Disease: A possible Marker of Disease Activity - H. Ishida; H. Shinohara; T. Nagata; S. Nishikawa; Y. Wakano (Mediators of Inflammation)
The activity of phospholipase A2 in human gingival crevicular fluid (GCF) associated with periodontal disease was demonstrated. Based upon the presence or absence of bleeding on probing (BOP), which is a marker for the disease activity, there were higher levels of the enzyme activity in BOP positive, than in negative sites. When the BOP positive sites became negative after periodontal therapy, the enzyme activity decreased dramatically to almost undetectable levels. There were no significant differences between the activity before and after treatment when the BOP positive sites remained unchanged. These results suggest that the activity in GCF reflects periodontal disease conditions and that it can be used as a marker for disease activity.